الأمة والمواطنة في وثيقة المدينة: تحليل الأسس والمعايير الدستورية ودورها في تعزيز التعايش الحضاري - Baidar Mohammed Mohammed Hasan; Dina Imad; Mohamed Mahmoud El Gammal (Universiti Sains Islam Malaysia, 2025)
Indexed by Scopus/MyCite